1989
DOI: 10.1080/14640748908402385
|View full text |Cite
|
Sign up to set email alerts
|

“Enacted” Auditory Images are Ambiguous; “Pure” Auditory Images are Not

Abstract: Previous research indicates that visual images are inherently unambiguous. The present study extends this argument to auditory imagery. In Experiment 1, subjects were able to reinterpret an imaged ambiguous auditory figure, but covert subvocalization apparently aided this reinterpretation. When subvocalization was blocked, reinterpretations were eliminated. Experiments 2 and 3 generalize this finding to different procedures and stimuli. Experiment 4 explores further the role of subvocalization, by showing that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 30 publications
6
48
0
Order By: Relevance
“…This transformation process persists throughout the repetition procedure, leading to perceptual transitions from one speech form to another. Although verbal transformations have mainly been studied as a purely acoustical/auditory effect (e.g., MacKay, Wulf, Yin, & Abrams, 1993;Pitt & Shoaf, 2001Warren, 1961), it has been shown that the effect occurs not only during a purely auditory procedure but also during an overt or covert repetition procedure (Reisberg, Smith, Baxter, & Sonenshine, 1989;Sato, Schwartz, Abry, Cathiard, & Loevenbruck, 2006;Smith, Reisberg, & Wilson, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…This transformation process persists throughout the repetition procedure, leading to perceptual transitions from one speech form to another. Although verbal transformations have mainly been studied as a purely acoustical/auditory effect (e.g., MacKay, Wulf, Yin, & Abrams, 1993;Pitt & Shoaf, 2001Warren, 1961), it has been shown that the effect occurs not only during a purely auditory procedure but also during an overt or covert repetition procedure (Reisberg, Smith, Baxter, & Sonenshine, 1989;Sato, Schwartz, Abry, Cathiard, & Loevenbruck, 2006;Smith, Reisberg, & Wilson, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…With this production procedure, the number of verbal transformations has been shown to gradually decrease from a condition of complete externalization to one of complete internalization, when subarticulation is blocked by a concurrent articulatory task, through a condition of partial externalization (i.e., whispering, mouthing; Reisberg et al, 1989). Sato and colleagues (2006) further showed that verbal transformations are specifically influenced by articulatory synergies.…”
Section: Introductionmentioning
confidence: 99%
“…While verbal transformations have initially been studied as a pure auditory perceptual effect, they appear to occur also when subjects repeatedly utter the speech stimulus in both an overt and a covert mode (Reisberg et al, 1989;Smith et al, 1995;Sato et al, 2006). With this production procedure, the number of verbal transformations has been shown to gradually decrease from a condition of complete externalization to one of complete internalization, when subarticulation is blocked by a concurrent articulatory task, through a condition of partial externalization (i.e., whispering, mouthing; Reisberg et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a wide variety of auditory imagery tasks rely on motoric representations of speech output (Reisberg, Smith, Baxter, & Sonenshine, 1989;Smith, Reisberg, & Wilson, 1992;Smith, Wilson, & Reisberg, 1995). Thus, the special processing abilities conferred by imitatibility may contribute even to off-line cognitive tasks.…”
Section: Off-line Uses Of Imitatibilitymentioning
confidence: 99%